Analisis kinerja BLUD pada puskesmas Nagaswidak dengan metode balanced scorecard - Zima Anggraini, Selly; Trisninawati, Trisninawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This researcher aims to determine performance analysis using the Balanced Scorecard method as a Performance Assessment Measuring Tool at the Nagaswidak Health Center. Researchers used qualitative research methods. The sample in this study is the Nagaswidak health center. For data collection using observation, documentation and interviews. The analytical technique used is descriptive analysis by describing the data that has been collected. internal business, learning and growth perspective, customer perspective. The results showed that the four perspectives in the balanced scorecard of the Nagaswi Health Center achieved a score of 77.78% which was in the range of 60 <80%. This shows that the performance of the Nagaswidak Health Center as a whole is in the category "good"..